Huntingtin and the Synapse - Barron, Jessica C.; Hurley, Emily P.; Parsons, Matthew P. (Frontiers in Cellular Neuroscience, 2021)
Huntington disease (HD) is a monogenic disease that results in a combination of motor, psychiatric and cognitive symptoms. HD is caused by a CAG trinucleotide repeat expansion in the huntingtin (HTT) gene, which results in the production of a pathogenic mutant HTT protein (mHTT). Although there is no cure at present for HD, a number of RNA-targeting therapies have recently entered clinical trials which aim to lower mHTT production through the use of antisense oligonucleotides (ASOs) and RNAi. However, many of these treatment strategies are non-selective in that they cannot differentiate between non-pathogenic wild type HTT (wtHTT) and the mHTT variant. As HD patients are already born with decreased levels of wtHTT, these genetic therapies may result in critically low levels of wtHTT. The consequence of wtHTT reduction in the adult brain is currently under debate, and here we argue that wtHTT loss is not well-tolerated at the synaptic level. Synaptic dysfunction is an extremely sensitive measure of subsequent cell death, and is known to precede neurodegeneration in numerous brain diseases including HD. The present review focuses on the prominent role of wtHTT at the synapse and considers the consequences of wtHTT loss on both pre- and postsynaptic function. We discuss how wtHTT is implicated in virtually all major facets of synaptic neurotransmission including anterograde and retrograde transport of proteins to/from terminal buttons and dendrites, neurotransmitter release, endocytic vesicle recycling, and postsynaptic receptor localization and recycling. We conclude that wtHTT presence is essential for proper synaptic function.